Fabrication and characterization of Si1−xGex nanocrystals in as-grown and annealed structures: a comparative study - Sultan, Muhammad Taha; Maraloiu, Adrian Valentin; Stavarache, Ionel; Gudmundsson, Jón Tómas; Manolescu, Andrei; Teodorescu, Valentin Serban; Ciurea, Magdalena Lidia; Svavarsson, Halldór Gudfinnur (Beilstein Journal of Nanotechnology, 2019)
Multilayer structures comprising of SiO2/SiGe/SiO2 and containing SiGe nanoparticles were obtained by depositing SiO2 layers using reactive direct current magnetron sputtering (dcMS), whereas, Si and Ge were co-sputtered using dcMS and high-power impulse magnetron sputtering (HiPIMS). The as-grown structures subsequently underwent rapid thermal annealing (550–900 °C for 1 min) in N2 ambient atmosphere. The structures were investigated using X-ray diffraction, high-resolution transmission electron microscopy together with spectral photocurrent measurements, to explore structural changes and corresponding properties. It is observed that the employment of HiPIMS facilitates the formation of SiGe nanoparticles (2.1 ± 0.8 nm) in the as-grown structure, and that presence of such nanoparticles acts as a seed for heterogeneous nucleation, which upon annealing results in the periodically arranged columnar self-assembly of SiGe core–shell nanocrystals. An increase in photocurrent intensity by more than an order of magnitude was achieved by annealing. Furthermore, a detailed discussion is provided on strain development within the structures, the consequential interface characteristics and its effect on the photocurrent spectra.
Keywords: grazing incidence XRD (GIXRD); high-power impulse magnetron sputtering (HiPIMS); HRTEM; magnetron sputtering; photocurrent spectra; SiGe nanocrystals in SiO2/SiGe/SiO2 multilayers; STEM-HAADF; TEM

(untitled) - Tevaarwerk, E.; Rugheimer, P.; Castellini, O. M.; Keppel, D. G.; Utley, S. T.; Savage, D. E.; Lagally, M. G.; Eriksson, M. A. (Appl. Phys. Lett., 2002)

(untitled) - Buljan, M.; Pinto, S. R. C.; Kashtiban, R. J.; Rolo, A. G.; Chahboun, A.; Bangert, U.; Levichev, S.; Holý, V.; Gomes, M. J. M. (J. Appl. Phys., 2009)

(untitled) - Mihalache, D. (J. Optoelectron. Adv. Mater., 2011)

CAS 2012 (International Semiconductor Conference) - Lepadatu, A. M.; Stavarache, I.; Maraloiu, A.; Palade, C.; Serban, T. V.; Magdalena, C. L. (Sinaia, Romania, 15.10.2012-17.10.2012, 2012)

(untitled) - Pan, S. W.; Zhou, B.; Chen, S. Y.; Li, C.; Huang, W.; Lai, H. K. (Appl. Surf. Sci., 2011)

(untitled) - Tuğay, E.; Ilday, S.; Turan, R.; Finstad, T. G. (J. Lumin., 2014)

(untitled) - Vieira, E. M. F.; Toudert, J.; Rolo, A. G.; Parisini, A.; Leitão, J. P.; Correia, M. R.; Franco, N.; Alves, E.; Chahboun, A.; Martín-Sánchez, J.; Serna, R.; Gomes, M. J. M. (Nanotechnology, 2017)

(untitled) - Kepa, J.; Stesmans, A.; Afanas’ev, V. V. (Appl. Surf. Sci., 2014)

(untitled) - Houssa, M.; Pourtois, G.; Meuris, M.; Heyns, M. M.; Afanas’ev, V. V.; Stesmans, A. (Microelectron. Eng., 2011)

(untitled) - Madia, O.; Nguyen, A. P. D.; Thoan, N. H.; Afanas’ev, V.; Stesmans, A.; Souriau, L.; Slotte, J.; Tuomisto, F. (Appl. Surf. Sci., 2014)

(untitled) - Tsetseris, L.; Pantelides, S. T. (Microelectron. Eng., 2011)

(untitled) - Lepadatu, A.-M.; Slav, A.; Palade, C.; Dascalescu, I.; Enculescu, M.; Iftimie, S.; Lazanu, S.; Teodorescu, V. S.; Ciurea, M. L.; Stoica, T. (Sci. Rep., 2018)

(untitled) - Pinto, S. R. C.; Kashtiban, R. J.; Rolo, A. G.; Buljan, M.; Chahboun, A.; Bangert, U.; Barradas, N. P.; Alves, E.; Gomes, M. J. M. (Thin Solid Films, 2010)

(untitled) - Stavarache, I.; Lepadatu, A.-M.; Stoica, T.; Ciurea, M. L. (Appl. Surf. Sci., 2013)

(untitled) - Choi, W. K.; Kanakaraju, S.; Shen, Z. X.; Li, W. S. (Appl. Surf. Sci., 1999)

(untitled) - Jie, Y. X.; Wu, X.; Huan, C. H. A.; Wee, A. T. S.; Guo, Y.; Zhang, T. J.; Pan, J. S.; Chai, J.; Chua, S. J. (Surf. Interface Anal., 1999)

(untitled) - Vieira, E. M. F.; Pinto, S. R. C.; Levichev, S.; Rolo, A. G.; Chahboun, A.; Buljan, M.; Barradas, N. P.; Alves, E.; Bernstorff, S.; Conde, O.; Gomes, M. J. M. (Microelectron. Eng., 2011)

(untitled) - Ray, S. K.; Das, S.; Singha, R. K.; Manna, S.; Dhar, A. (Nanoscale Res. Lett., 2011)

(untitled) - Chew, H. G.; Choi, W. K.; Foo, Y. L.; Zheng, F.; Chim, W. K.; Voon, Z. J.; Seow, K. C.; Fitzgerald, E. A.; Lai, D. M. Y. (Nanotechnology, 2006)

(untitled) - Zschintzsch, M.; von Borany, J.; Jeutter, N. M.; Mücklich, A. (Nanotechnology, 2011)

(untitled) - Barradas, N. P.; Alves, E.; Vieira, E. M. F.; Parisini, A.; Conde, O.; Martín-Sánchez, J.; Rolo, A. G.; Chahboun, A.; Gomes, M. J. M. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2014)

(untitled) - Sultan, M. T.; Gudmundsson, J. T.; Manolescu, A.; Stoica, T.; Ciurea, M. L.; Svavarsson, H. G. (Appl. Surf. Sci., 2019)

(untitled) - Sultan, M. T.; Manolescu, A.; Gudmundsson, J. T.; Torfason, K.; Alexandru Nemnes, G.; Stavarache, I.; Logofatu, C.; Teodorescu, V. S.; Ciurea, M. L.; Svavarsson, H. G. (Appl. Surf. Sci., 2019)

(untitled) - Palade, C.; Slav, A.; Lepadatu, A. M.; Maraloiu, A. V.; Dascalescu, I.; Iftimie, S.; Lazanu, S.; Ciurea, M. L.; Stoica, T. (Appl. Phys. Lett., 2018)

(untitled) - Helmersson, U.; Lattemann, M.; Bohlmark, J.; Ehiasarian, A. P.; Gudmundsson, J. T. (Thin Solid Films, 2006)

(untitled) - Lundin, D.; Sarakinos, K. (J. Mater. Res., 2012)

(untitled) - Gudmundsson, J. T. (Vacuum, 2010)

(untitled) - Gudmundsson, J. T.; Brenning, N.; Lundin, D.; Helmersson, U. (J. Vac. Sci. Technol., A, 2012)

(untitled) - Samuelsson, M.; Lundin, D.; Jensen, J.; Raadu, M. A.; Gudmundsson, J. T.; Helmersson, U. (Surf. Coat. Technol., 2010)

(untitled) - Alami, J.; Persson, P. O. Å.; Music, D.; Gudmundsson, J. T.; Bohlmark, J.; Helmersson, U. (J. Vac. Sci. Technol., A, 2005)

(untitled) - Aqua, J.-N.; Berbezier, I.; Favre, L.; Frisch, T.; Ronda, A. (Phys. Rep., 2013)

(untitled) - Stavarache, I.; Maraloiu, V. A.; Negrila, C.; Prepelita, P.; Gruia, I.; Iordache, G. (Semicond. Sci. Technol., 2017)

(untitled) - Patterson, A. L. (Phys. Rev., 1939)

(untitled) - Mogaddam, N. A. P.; Alagoz, A. S.; Yerci, S.; Turan, R.; Foss, S.; Finstad, T. G. (J. Appl. Phys., 2008)

(untitled) - Ciurea, M. L.; Lepadatu, A. M. (Dig. J. Nanomater. Bios., 2015)

(untitled) - Dismukes, J. P.; Ekstrom, L.; Paff, R. J. (J. Phys. Chem., 1964)

(untitled) - Sultan, M. T.; Gudmundsson, J. T.; Manolescu, A.; Teodorescu, V. S.; Ciurea, M. L.; Svavarsson, H. G. (Nanotechnology, 2019)

(untitled) - Bertran, E.; Sharma, S. N.; Viera, G.; Costa, J.; St'ahel, P.; Cabarrocas, P. R. i. (J. Mater. Res., 1998)

(untitled) - Bahariqushchi, R.; Raciti, R.; Kasapoğlu, A. E.; Gür, E.; Sezen, M.; Kalay, E.; Mirabella, S.; Aydinli, A. (Nanotechnology, 2018)

(untitled) - Zatryb, G.; Podhorodecki, A.; Misiewicz, J.; Cardin, J.; Gourbilleau, F. (Nanoscale Res. Lett., 2013)

(untitled) - Liao, P. H.; Hsu, T. C.; Chen, K. H.; Cheng, T. H.; Hsu, T. M.; Wang, C. C.; George, T.; Li, P. W. (Appl. Phys. Lett., 2014)

(untitled) - Zatryb, G.; Misiewicz, J.; Wilson, P. R. J.; Wojcik, J.; Mascher, P.; Podhorodecki, A. (Thin Solid Films, 2014)

(untitled) - Zhang, M.; Cai, R.; Zhang, Y.; Wang, C.; Wang, Y.; Ross, G. G.; Barba, D. (Mater. Charact., 2014)

(untitled) - Qin, G. G.; Li, Y. J. (Phys. Rev. B, 2003)

(untitled) - Yakimov, A. I.; Kirienko, V. V.; Armbrister, V. A.; Dvurechenskii, A. V. (Semicond. Sci. Technol., 2014)

(untitled) - Brown, W. D.; Khaliq, M. A. (Thin Solid Films, 1990)

(untitled) - Dashiell, M. W.; Denker, U.; Müller, C.; Costantini, G.; Manzano, C.; Kern, K.; Schmidt, O. G. (Appl. Phys. Lett., 2002)

(untitled) - Nazarov, A. N.; Lysenko, V. S.; Nazarova, T. M. (Semicond. Phys., Quantum Electron. Optoelectron., 2008)

(untitled) - Nikitin, T.; Khriachtchev, L. (Nanomaterials, 2015)

(untitled) - Wolkin, M. V.; Jorne, J.; Fauchet, P. M.; Allan, G.; Delerue, C. (Phys. Rev. Lett., 1999)

(untitled) - Szekeres, A.; Alexandrova, S. (Vacuum, 1996)

(untitled) - Puzder, A.; Williamson, A. J.; Grossman, J. C.; Galli, G. (J. Chem. Phys., 2002)

(untitled) - López, M.; Garrido, B.; Garcı́a, C.; Pellegrino, P.; Pérez-Rodrı́guez, A.; Morante, J. R.; Bonafos, C.; Carrada, M.; Claverie, A. (Appl. Phys. Lett., 2002)

(untitled) - Hadjisavvas, G.; Kelires, P. C. (Phys. Rev. Lett., 2004)

(untitled) - Hadjisavvas, G.; Remediakis, I. N.; Kelires, P. C. (Phys. Rev. B, 2006)

(untitled) - Ye, H.; Yu, J. (Sci. Technol. Adv. Mater., 2014)

(untitled) - Ekpe, S. D.; Jimenez, F. J.; Field, D. J.; Davis, M. J.; Dew, S. K. (J. Vac. Sci. Technol., A, 2009)

(untitled) - Papa, F.; Gerdes, H.; Bandorf, R.; Ehiasarian, A. P.; Kolev, I.; Braeuer, G.; Tietema, R.; Krug, T. (Thin Solid Films, 2011)

(untitled) - Čapek, J.; Hála, M.; Zabeida, O.; Klemberg-Sapieha, J. E.; Martinu, L. (J. Phys. D: Appl. Phys., 2013)